Modelo de gestão aplicado à metrologia legal: proposta do modelo brasileiro para arqueação de tanques - Rezende, Raimundo Alves de (2004)
There isn t a Legal Metrology regulation in Brasil for measurement storage tanks, such as other activities that received a regulatory order by Inmetro. Also, there isn t anything like that by Conmetro; but, rules and regulations are established by ANP, Receita da Fazenda Federal and requirement from companies, that are interested in process control. Inmetro was designed, a long time ago, to be a measurement storage tanks servicing, receiving this tasks from INT and INPM. Inmetro is working in this area since 1973. Using procedures established by your antecedents and has improved on the job training. After quality subject and a new law for petroleum area, and other motivation agents, it is necessary to review a lot of things about this. We ve just studied a lot of subjects, standards and other documents of importance organization s for tanks calibration methods around the world. We ve seen that there are some new technology just standardized. We did some calculations of real tanks and we are presenting the volumetrie table and the storage tank s certificate. We ve studied looking for to discover the best way to improve our servicing area. Meeting a great number of attendances, reducing measurement uncertainty, based on the best standards applications, like our partner countries are doing. Ending this research, we hope that everybody can find this subject, we hope this area in Brazil meet a regulatory order by Inmetro. And that comes true the metrological states organizations will be allowed and able to help us, also in this deal.